Dietary protein requirement level of tinfoil barb (Barbonymus schwanenfeldii Bleeker 1853) fry - Mohd Puaad, Nuruljannah; Mohd Salleh, Kamarudin; Fadhil, Syukri; Cruz, Clement R. (John Wiley & Sons, 2022)
An 8-week feeding trial was conducted to determine the optimal dietary protein requirement for tinfoil barb (Barbonymus schwanenfeldii) fry. Six isocaloric practical test diets (17 kJ g−1 gross energy) were formulated to contain 25%, 30%, 35%, 40%, 45% and 50% protein. Fry (0.40 ± 0.03 g) were randomly stocked in eighteen 60 L glass aquaria at 25 fish per aquarium. Each aquarium was fitted with an individual recirculation system. Each test diet was randomly assigned to three aquaria (triplicates), and the fish were fed twice a day until satiation. The results showed that survival was not significantly affected by the protein level. Weight gain was significantly higher at 50% dietary protein compared with those of lower levels. Fish fed with 50% protein also showed a significantly higher (p < 0.05) specific growth rate than fish fed with 25%–40% protein. Feed efficiency improved with the increase in dietary protein level. Feed conversion ratio (FCR) was 1.29 when fry were fed 50% dietary protein, whereas fry fed 25%–35% protein had FCR of 1.7–2.0. No histopathologic changes in the liver and intestine were observed among all dietary treatments. The results indicated that tinfoil barb fry required a high 50% protein for best growth performance and feed efficiency.